Flexure of continuous HSC beams with external CFRP tendons: effects of fibre elastic modulus and steel ratio - Lou, Tiejiong (2014)
The results of a theoretical study on the flexural behaviour of continuous high-strength concrete (HSC) beams prestressed with external fibre reinforced polymer (FRP) tendons are presented. A previously developed numerical model is extended to the analysis of continuous HSC beams with external FRP tendons. A numerical test is conducted on two-span externally prestressed beams made of HSC with compressive strength of 90 MPa. The external tendons are assumed to be carbon FRP (CFRP) composites covering a wide range of modulus of elasticity. Various levels of nonprestressed steel ratio are used. Comprehensive aspects of behaviour of such type of beams are examined. The results show that CFRP with high elastic modulus of 500 GPa mobilizes quite different structural responses compared to those with normal elastic modulus, and that the amount of nonprestressed steel affects remarkably the behaviour of such beams. The study also indicates that some moment redistribution knowledge valid for conventional continuous concrete beams may not be applicable to continuous HSC beams with external FRP tendons.